Mathematics formative assessment - Keeley, Page.; Tobey, Cheryl Rose. (Thoudand Oaks, Calif. : Corwin Press, 2011)
"There is a substantive body of research that indicates formative assessment can significantly improve student learning. Yet, this same research shows that the features of formative assessment that impact student achievement are sadly missing from many classrooms (Black, et al., 2003). This book provides teachers with guidance and suggestions for using formative assessment to improve teaching and learning in the mathematics classroom, and identifies and describes practical techniques teachers can use to build a rich repertoire of formative assessment strategies. The acronym, FACT, is used to label the techniques included in this book. FACT stands for Formative Assessment Classroom Technique. Through the varied use of FACTs, explicitly tied to a purpose for gathering information about or promoting students--thinking and learning, teachers can focus on what works best for learning and design or modify lessons to fit the needs of the students"--
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching; Educational evaluation; EDUCATION / Teaching Methods & Materials / Mathematics